For Women Only? Reconsidering Gender Requirements for Uterine Transplantation Recipients - Wagner, Darren (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
Uterine transplantation is an experimental procedure currently available only to cisgender women recipients suffering from absolute uterine factor infertility. Clinicians, researchers, and advocates have advanced the possibility of providing these quality-of-life transplantations to transgender women. This article examines the ethical and practical implications of removing sex- and gender-based requirements entirely for uterine transplantation recipients. Given the significant costs and risks, and the modest quality-of-life benefits, ethical arguments against offering uterine transplantations to people who do not identify as women but are otherwise suitable recipients are dubious and prejudicial. Successful uterine transplantations with non-women recipients could potentially diminish the socio-cultural connection between uterine functionality and womanhood, which is a key motivation for women now seeking this high-risk procedure.